PENGARUH LITERASI KEUANGAN DAN INKLUSI KEUANGAN TERHADAP PERILAKU KEUANGAN NASABAH (STUDI KASUS PADA NASABAH BANK SYARIAH INDONESIA KANTOR CABANG PEMBANTU (KCP) MEULABOH IMAM BONJOL) - Aristia, Shinta; Damrus, Damrus; Zhafira, Nabila Hilmy (Jurnal Sains Riset, 2024)
The aim of this research is to understand how financial literacy and financial inclusion influence customer financial behavior. Meanwhile, this research uses quantitative methods with primary data. Sampling was carried out using a non-probability sampling method with purposive sampling type, and the sample was calculated using the Slovin formula to obtain 100 respondents. The data was collection online by distributing questionnaires to respondents via Google Forms. The data was then analyzed using data analysis techniques, with SPSS version 20 software. The results of this research show that the two independent variables, namely financial literacy and financial inclusion, have a positive and significant impact on financial behavior